The Biology of Senegalese Grasshopper (Oedaleus Senegalensis, Krauss, 1877) (Orthoptera: Acrididae) - Elamin, Abdelmanan E. H; Abdalla, Abdalla M; El Naim, Ahmed M (International Journal of Advances in Life Science and Technology, 2014)
The Senegalese grasshopper, Oedaleus senegalensis (Orthoptera: Acrididae) is known as pest of economic importance which cause damage to millet and sorghum crops besides pastures in western Sudan. The study was done to investigate the biology of the insect on its natural habitat. Observations in the field were made twice/ week, from April-November each year for three continuous seasons 2006/2007, 2007/2008 and 2008/2009, in two selected sites one around Gellabiya village in North Kordofan State west Elobeid town. The other was around Kuik village in South Kordofan State north Kadugli town. The nymphs and the adults were collected by sweep net from the field and transferred to the laboratory for study. Female adults of the Senegalese grasshopper were dissected and examined under binocular Microscope (Paralux, Optigue de précision CE 0602397) to investigate the fecundity through ovarioles numbers and function. Duration of each of the developmental stages of the pest was determined. Results showed that the mean number of ovarioles is 36 / ovary and two egg pods were laid /female. The mean fecundity was 44 eggs. The female laid eggs twice during life cycle. Ovariole function average was 76% in the first laying and 36% in the second laying. Mean developmental duration after hatching of O. senegalensis to adult (nymphal instars) was 25 day. The respective nymphal duration from the 1st to the 5th instar was 4, 5, 5, 5, and 6 days, respectively.